2009
DOI: 10.1088/0004-637x/700/2/l78
|View full text |Cite
|
Sign up to set email alerts
|

Stellar Kinematic Constraints on Galactic Structure Models Revisited: Bar and Spiral Arm Resonances

Abstract: We study the phase space available to the local stellar distribution using a Galactic potential consistent with several recent observational constraints. We find that the induced phase space structure has several observable consequences. The spiral arm contribution to the kinematic structure in the solar neighborhood may be as important as the one produced by the Galactic bar. We suggest that some of the stellar kinematic groups in the solar neighborhood, like the Hercules structure and the kinematic branches,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
127
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(132 citation statements)
references
References 38 publications
5
127
0
Order By: Relevance
“…The radial dispersion is not very strong in M 67, but distorts what would be a box orbit. Thus, a moderate spiral potential has important effects in the kinematics of orbits near the Galactic plane, as is the case in M 67, and in general, as is the case for the solar-neighborhood stars (Antoja et al 2009). This result holds for the allowed variations in proper motion, radial velocity and distance, because the most important parameter that affects the orbit is the mass of the spiral arms.…”
Section: The Galactic Orbit Of M 67mentioning
confidence: 93%
“…The radial dispersion is not very strong in M 67, but distorts what would be a box orbit. Thus, a moderate spiral potential has important effects in the kinematics of orbits near the Galactic plane, as is the case in M 67, and in general, as is the case for the solar-neighborhood stars (Antoja et al 2009). This result holds for the allowed variations in proper motion, radial velocity and distance, because the most important parameter that affects the orbit is the mass of the spiral arms.…”
Section: The Galactic Orbit Of M 67mentioning
confidence: 93%
“…One striking example is the HR 1614 stream (Eggen 1978;Feltzing & Holmberg 2000;De Silva et al 2007b). Stellar streams can also originate from dynamical effects within the discs that are due to resonances with the bars or spiral arms (Dehnen 2000;Antoja et al 2009). Analysis of high-resolution spectra of nearby F and G dwarf stars has revealed that the stars in the Hercules stream have a wide range of stellar ages, metallicities, and element abundances (Bensby et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical approaches (e.g., Quillen 2003;Quillen & Minchev 2005;Chakrabarty 2007;Minchev & Quillen 2007;Antoja et al 2009;Minchev & Famaey 2010;McMillan 2013) have been tested to identify the dominant mechanism that drives the evolution of the velocity distribution of the stars in the solar neighborhood. In their models, they investigated the cases of the resonances that would be caused by either the Galactic bar, the spiral structure, or both.…”
Section: Introductionmentioning
confidence: 99%